2023
DOI: 10.1038/s41467-023-39260-4
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved-Cl2 triggered redox reaction enables high-performance perovskite solar cells

Abstract: Constructing 2D/3D perovskite heterojunctions is effective for the surface passivation of perovskite solar cells (PSCs). However, previous reports that studying perovskite post-treatment only physically deposits 2D perovskite on the 3D perovskite, and the bulk 3D perovskite remains defective. Herein, we propose Cl2-dissolved chloroform as a multifunctional solvent for concurrently constructing 2D/3D perovskite heterojunction and inducing the secondary growth of the bulk grains. The mechanism of how Cl2 affects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…39,40 Notably, the exposure of the 3D for the secondary growth of 3D perovskite grains (∼5 μm). 56 The easy Cl 2 permeation enables effective overall defect passivation within the 3D perovskite layers as well as the buried interface, thus leading to a high PCE of 24.21% in the Cl-incorporated target devices. The success of these prototypal bilayer 2D-3D PHSs adopting phenyl and linear alkyl spacer cations triggered further molecular structural design by decorating various functional groups to enable more durable and conductive 2D perovskite capping layers.…”
Section: Evolution Roadmap Of Bilayer 2d-3d Phssmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Notably, the exposure of the 3D for the secondary growth of 3D perovskite grains (∼5 μm). 56 The easy Cl 2 permeation enables effective overall defect passivation within the 3D perovskite layers as well as the buried interface, thus leading to a high PCE of 24.21% in the Cl-incorporated target devices. The success of these prototypal bilayer 2D-3D PHSs adopting phenyl and linear alkyl spacer cations triggered further molecular structural design by decorating various functional groups to enable more durable and conductive 2D perovskite capping layers.…”
Section: Evolution Roadmap Of Bilayer 2d-3d Phssmentioning
confidence: 99%
“…Compared to their pure iodide counterparts, Br/Cl-incorporated 2D perovskites are thermodynamically more stable due to a lower formation energy from the relaxed lattice strain . For instance, the post-treatment of HABr and OABr gave rise to mixed-halide quasi-2D perovskite capping layers of HA 2 FAPb 2 Br 2 I 5 ( n = 2) and OA 2 FAPb 2 Br 2 I 5 ( n = 2), respectively. , Notably, the exposure of the 3D perovskite layer to the corrosive IPA with a high solubility of FAI tends to create a PbI 2 -rich surface that facilitates the formation of 2D perovskite of HA 2 PbI 2 Br 2 ( n = 1) by the chemical reaction between PbI 2 and HABr at the surface, while the use of nonreactive CF results in quasi-2D perovskite of HA 2 FA n ‑1 Pb n I 3 n ‑1 Br 2 ( n ≥ 2) upon the gradual intercalation of HABr into the crystal lattices of FAPbI 3 . , Moreover, oxidative Cl 2 generated in the fresh CF solvent after light soaking could offer a viable Cl source for the successful preparation of Cl-doped bilayer 2D-3D PHSs, where the identified Cl 2 /I- redox reaction triggers the Ostwald ripening for the secondary growth of 3D perovskite grains (∼5 μm) . The easy Cl 2 permeation enables effective overall defect passivation within the 3D perovskite layers as well as the buried interface, thus leading to a high PCE of 24.21% in the Cl-incorporated target devices.…”
Section: Evolution Roadmap Of Bilayer 2d-3d Phssmentioning
confidence: 99%
“…The presence of hexylammonium bromide in the solvent enables a reaction with the remaining PbI 2 , resulting in the formation of surface 2D/3D heterojunctions. 28 Wu et al reported that incorporating a dimethyl sulfoxide (DMSO) solution into the PbI 2 layer facilitates the formation of the PbI 2 framework. 29 However, DMSO evaporates during high-temperature annealing, resulting in residual lead iodide on the surface of the perovskite absorber layer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Luo et al suggested that the 3D perovskite can undergo a reaction with Cl 2 -dissolved chloroform, resulting in an ionic exchange of Cl/I and promoting the Ostwald ripening process of the bulk grains. The presence of hexylammonium bromide in the solvent enables a reaction with the remaining PbI 2 , resulting in the formation of surface 2D/3D heterojunctions . Wu et al reported that incorporating a dimethyl sulfoxide (DMSO) solution into the PbI 2 layer facilitates the formation of the PbI 2 framework .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the construction of 2D/3D perovskite heterojunction structures primarily involves regrowing a layer of two-dimensional perovskite on the interface of the 3D perovskite. This sequential growth process allows for the formation of a 2D/3D heterojunction structure. For example, Yoo et al utilized hexylammonium bromide (HABr) as a precursor for 2D perovskites to construct the 2D/3D structure. However, in this construction strategy, the 2D perovskite capping layer is likely to be physically overlaid on the 3D perovskite, resulting in only weak interface interactions existing between the 2D and 3D perovskite layers .…”
Section: Introductionmentioning
confidence: 99%